트랙터 부착형 다기능 작업기의 비용 및 포장능률 비교를 통한 경제성 분석 - 김승준; Seungjun Kim; 장문경; Moonkyeong Jang; 남주석; Juseok Nam (농업생명환경연구, 2022)
In this study, an economic analysis of the cost and field capacity was conducted to prove the validity of developing and distributing a tractor-mounted multi-working machine. The cases of using a multi-working machine and individual working machines were compared. The results showed that the total hourly cost of the multi-working machine was 308,805 KRW. Compared with individual working machines, the tractor-mounted multi-working machine can save 53.5% of the total hourly cost. The field capacity for the multi-working machine was 12 ares/hour. This is 60.0% higher than that of individual working machines. The cost per 10 ares working area was calculated using the hourly total cost and field capacity. The cost per 10 ares working area for the multi-working machine is 257,337 KRW, meaning that the multi-working machine can save 71.0% of the cost compared with individual working machines. Therefore, it is concluded that the economic validity of the multiworking machine is high.